2017
DOI: 10.1007/s10784-017-9366-9
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development Goals and REDD+: assessing institutional interactions and the pursuit of synergies

Abstract: This paper analyzes potential synergies between two recent sustainable development initiatives, namely the Sustainable Development Goals (SDGs) and reducing emissions from deforestation and forest degradation (REDD?), a climate mitigation mechanism negotiated under the auspices of the United Nations Framework Convention on Climate Change. The paper elaborates a conceptual framework based on institutional interactions and distinguishes core, complementary, and supplementary synergies that may be realized betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Leakage also relates to the subject of institutional interactions. In an increasingly interdependent world, institutions aiming to prevent or address environmental issues frequently interact with one another and produce impacts elsewhere (Kissinger et al 2011, Visseren-Hamakers 2015, Bastos Lima et al 2017. Interactions may exist even within a single institutional framework, as in the case of the Sustainable Development Goals (Ehrensperger et al 2019).…”
Section: Leakage As a Governance Challenge: Institutional Fit And Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Leakage also relates to the subject of institutional interactions. In an increasingly interdependent world, institutions aiming to prevent or address environmental issues frequently interact with one another and produce impacts elsewhere (Kissinger et al 2011, Visseren-Hamakers 2015, Bastos Lima et al 2017. Interactions may exist even within a single institutional framework, as in the case of the Sustainable Development Goals (Ehrensperger et al 2019).…”
Section: Leakage As a Governance Challenge: Institutional Fit And Intmentioning
confidence: 99%
“…There is extensive literature on policy interactions and institutional interplay that catalog various ways in which policies may change, support or undermine one another: see, e.g. Lambin et al (2014) and Lambin and Thorlakson (2018) for reviews related to land use in the Tropics, Visseren-Hamakers (2015) and Bastos Lima et al (2017) for discussions on institutional synergies and interactions, and Holzinger et al (2008) on policy harmonization, learning and regulatory competition. While this literature shows that policy interactionswithin or across jurisdictions-are important for environmental outcomes, these mechanisms have rarely been linked to discussions on leakage and spillovers.…”
Section: Institutionsmentioning
confidence: 99%
“…Several interviewees mentioned the need for the EU to contribute to global dialogues on REDD+ or other multilateral processes that can link demand and supply-side measures, and suggested that the SDGs could provide a helpful framework for this process (potential synergies between REDD+ and the SDGs have also been noted by others, such as [82]). However, it was noted that there is no obvious existing UN fora where such a dialogue could take place, with little confidence expressed in the UNFF (in line with previous criticism, for example, [83]).…”
Section: Shifting Responsibility From South To North: Targeting Demand?mentioning
confidence: 99%
“…Such an approach attempts to find a balance between different land uses (Molua 2012:83), and is mainly promoted by those interested in REDD+ from a forest conservation perspective and its potential to deliver co-benefits, especially for biodiversity (for example, Potts et al 2013). Yet, as Sayer et al (2013) report, there are also differences in the conceptualisation of ecological landscapes, from those that exclusively focus on biogeographical characteristics to more recent perspectives that aim to reconcile conservation and development trade-offs (see, for example, Leventon et al 2014, andBastos-Lima et al (2017a) for an analysis of synergies between REDD+ and the Sustainable Development Goals). Given that there are unlikely to be significant overlaps between political jurisdictions and ecosystem boundaries, ecologicallybased landscape approaches necessarily involve a complex web of actors rather than a dominance of formal state administrations (van Oosten 2013).…”
Section: Figure 41 Conceptualisations Of Landscape Approaches To Redd+mentioning
confidence: 99%
“…Several interviewees mentioned the need for the EU to contribute to global dialogues on REDD+ or other multilateral processes that can link demand and supply-side measures, and suggested that the SDGs could provide a helpful framework for this process (potential synergies between REDD+ and the SDGs have also been noted by others, such as Bastos Lima et al 2017a). However, it was noted that there is no obvious existing UN fora where such a dialogue could take place, with little confidence expressed in the UNFF (in line with previous criticism, for example, Dimitrov 2005).…”
Section: From Fragmentation To Integration In Networked Eu Forest Govmentioning
confidence: 99%